(E)-4-Hydroxy-N '-(2-hydroxy-4-methoxybenzylidene)benzohydrazide monohydrate - Lair, N.M.; Ng, S.W.; Ali, Hapipah Mohd (International Union of Crystallography, 2009)
The Schiff base molecule of the title compound, C(15)H(14)N(2)O(4)center dot-H(2)O, adopts a trans configuration with respect to the C=N double bond; the Schiff base itself is almost planar (r. m. s. deviation for all non-H atoms = 0.040 angstrom). The amido N atom is the hydrogen-bond donor to the water molecule, which is the hydrogen-bond donor to the hydroxy groups of two neighboring molecules. One of the hydroxyl groups acts as an intramolecular and the other as an intermolecular hydrogenbond donor.